Rediscovering psychoanalysis : thinking and feeling, learning and forgetting - Ogden, Thomas H. (New library of psychoanalysis., 2008)
Winner of the 2010 Haskell Norman Prize for Outstanding Achievement in Psychoanalysis!Rediscovering Psychoanalysis demonstrates how, by attending to one's own idiosyncratic ways of thinking, feeling, and responding to patients, the psychoanalyst can develop a ""style"" of his or her own, a way of practicing that is a living process originating, to a large degree, from the personality and experience of the analyst. This book approaches rediscovering psychoanalysis from four vantage points derived from the author's experience as a clinician, a supervisor,